PEMASANGAN KATETER DENGAN KEJADIAN INFEKSI SALURAN KEMIH PADA PASIEN DI RUANG RAWAT INAP - Nababan, Tiarnida (Universitas Prima Indonesia, 2020)
Urinary tract infection (UTI) is a result of the development of microorganisms in the urinary tract, which in normal conditions do not contain bacteria, viruses, or other microorganisms. Urinary tract infections are also infections that occupy the second position that most often attacks the body after respiratory infections. The objective of the study was to identify the relationship between catheter placement and the incidence of urinary tract infections at Royal Prima hospital Medan. This is a correlation study (correlation study) on the patients suffering from urinary tract infections. The sampling technique used was a saturated sampling technique. Analysis research data using the Spearmen test. Based on the results of the study, it was found that the majority of catheter installation was in the category of good were 78%, and in the category of not good 22%, and 78% suffered from do not experience urinary tract infections, and 22% infection urinary tract. The results of the study of the Spearmen test showed that p-value = 0.00. It was found that there was a relationship between catheter insertion and the incidence of urinary tract infections in the inpatient room. The local nurses are suggested to improve the aseptic technique of care performed when catheterization is performed so that the incidence of urinary tract infections due to catheter installation can be avoided.